Radiosensitivity-Related Genes and Clinical Characteristics of Nasopharyngeal Carcinoma. - Dai, Yongmei; Zhang, Yue; Yang, Mi; Zhou, Liang; Pan, Hua; Xiao, Ting; Yuan, Lu; Wu, Yuting; Chen, Min; Chen, Longhua; Guan, Jian (BioMed Research International, 2020)
Background and Purpose. Radioresistance is one of the main obstacles limiting the therapeutic efficacy of chemoradiotherapy (CRT) and favorable patient prognoses, and the molecular mechanisms underlying this type of resistance remain unclear. The purpose of this study was to identify characteristic genes involved in chemoradiotherapy resistance in nasopharyngeal carcinoma (NPC). Materials and Methods. Clinicopathological data of 185 patients with NPC treated at Nanfang Hospital of Southern Medical University between January 2013 and December 2014 were retrospectively analyzed. SPSS statistical software was used to analyze the clinicopathological data related to radiotherapy efficacy. Three patients who achieved complete remission and three with disease progression after CRT were selected. Differentially expressed genes (DEGs) were screened via mRNA microarray analysis of primary diagnostic endoscopy specimens. Results. The peripheral blood leukocyte count, platelet count, and EBV-DNA copy number in NPC patients who were resistant to radiotherapy were higher than those in NPC patients who were sensitive to radiotherapy. The RobustRankAggreg (RRA) analysis method identified 392 DEGs, and the 66 most closely related genes among the DEGs were identified from the PPI network. Conclusion. The results of this study indicate that screening for DEGs and pathways in NPC using integrated in silico analyses can help identify a series of genetic and clinical signatures for NPC patients treated with neoadjuvant chemotherapy followed by concurrent chemoradiotherapy.